Government Block Holder Ownership, Sovereign Wealth Fund and Firm Performance - LIU, Kerry (Journal of Advanced Studies in Finance; Vol 7 No 2 (2016): JASF Volume VII Issue 2(14) Winter 2016, 2017)
Sovereign Wealth Funds (SWFs) have attracted attentions of global financial markets only since 2006. This paper is one of the earliest to study the performance of firms controlled by SWFs and how their performance relates to shareholding. My empirical evidence suggests that the SWF-controlled firms outperform other types of government firms and even perform better than non-government firms. The positive relation between SWF ownership and firm performance becomes negative as the shareholding reaches a high level. These findings are consistent with the characteristics and operating behavior of SWFs in financial markets. My findings contribute to the understanding and debates surrounding SWFs.
Keywords: sovereign wealth fund (SWF), government blockholder ownership, firm performance.